2012
DOI: 10.1002/ep.11620
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenization of copper catalyst for the oxidation of phenol, a common contaminant in industrial wastewater

Abstract: Advance oxidation process was employed as a pretreatment of industrial wastewater. For this purpose, the use of heavy metals as a catalyst is necessary but also complicated because homogeneous catalysts are difficult to recover after reaction process. The heterogenization of Cu(II) ions was proposed by taking advantage of the adsorptive characteristics of polymeric matrices. Crosslinked poly(4-vinylpyridine) of 2 and 25% and poly(D-glucosamine) were tested as supports of copper. Adsorption was employed to hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Large varieties of heterogeneous catalysts with transition metals as the active species have been reported for the catalytic degradation of phenol wastewater. [16][17][18][19][20] A phenol conversion of 95% and a TOC (total organic carbon) conversion of 45% were achieved when Fe-ZSM-5 zeolite membrane catalysts were applied in the catalytic wet peroxide oxidation of phenol by Yan et al 21 Wang et al 22 prepared composite nanospheres of hydrogel coated magnetic Fe 3 O 4 and tested for the catalytic wet peroxide oxidation of phenol and achieved a phenol conversion of 98% and a COD removal of 76%. Liou et al 23 reported the catalytic oxidation of phenol with CuO impregnated activated carbon and obtained over 90% COD removal.…”
Section: Introductionmentioning
confidence: 99%
“…Large varieties of heterogeneous catalysts with transition metals as the active species have been reported for the catalytic degradation of phenol wastewater. [16][17][18][19][20] A phenol conversion of 95% and a TOC (total organic carbon) conversion of 45% were achieved when Fe-ZSM-5 zeolite membrane catalysts were applied in the catalytic wet peroxide oxidation of phenol by Yan et al 21 Wang et al 22 prepared composite nanospheres of hydrogel coated magnetic Fe 3 O 4 and tested for the catalytic wet peroxide oxidation of phenol and achieved a phenol conversion of 98% and a COD removal of 76%. Liou et al 23 reported the catalytic oxidation of phenol with CuO impregnated activated carbon and obtained over 90% COD removal.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a heterogeneous catalyst (PVP 2 ‐Cu [II] catalyst) was used to oxidize phenol with hydrogen peroxide in a batch reactor. It converted 64% phenol, which is considered a promising outcome for phenol oxidation under harsh conditions 122 . The magnetic Fe 3 O 4 particles were another promising option of catalysts used for the catalysis of ozonation of drugs (sulfamethoxazole) by the ozone oxidation power.…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…It converted 64% phenol, which is considered a promising outcome for phenol oxidation under harsh conditions. 122 The magnetic Fe 3 O 4 particles were another promising option of catalysts used for the catalysis of ozonation of drugs (sulfamethoxazole) by the ozone oxidation power. This catalyst's magnetic property encourages its function in catalysis even if it is not the core of the whole process.…”
Section: Catalytic Oxidationmentioning
confidence: 99%
“…Copper (Cu) powders have excellent electrical and thermal conductivity, are inexpensive, and can be used in a variety of applications such as conductive inks, 1-5 electronic paste, 6,7 electrode materials, 8,9 electrical contact materials, 10,11 electromagnetic shielding materials 12 and chemical catalyst materials. 12,13 However, the most critical issue is that copper is extremely unstable, especially ultrafine Cu powders that can be easily oxidised, even at room temperature. After oxidation, electrical conductivity deteriorates dramatically, which severely limits the application of Cu powders.…”
Section: Introductionmentioning
confidence: 99%